Tuesday

January 27, 2015

January 27, 2015

Posted by **Justine** on Saturday, January 15, 2011 at 11:54pm.

- Algebra -
**Marth**, Sunday, January 16, 2011 at 12:22amx^2-6x-3=0

x = (-b +/- sqrt(b^2-4ac))/(2a)

x = (6 +/- sqrt(6^2 - 4(1)(-3)) ) / (2(1))

**Answer this Question**

**Related Questions**

algebra - Use the quadratic formula to find the roots of the equation. Round to ...

algebra - use the quadratic formula to find the roots of the equation. round to ...

Algebra II - Find the exact solution to 6x^2+1= -8x by using the Quadratic ...

Math - When you use the quadratic formula (x= -b+/=......) can you use that on ...

Math - I can't remember how you find the roots of quadratic equations other than...

Algebra - Given the roots, 1/2 and 4, find: (A) The quadratic equation 2x^2-9x+4...

math help - write the quadratic equation whose roots are -4 and -5 and whose ...

Algebra - Find the number of integer quadruples (a,b,c,d) with 0\leq a,b,c,d \...

Algebra - Find the number of integer quadruples (a,b,c,d) with 0\leq a,b,c,d \...

Algebra - For this equation x^(2) + x + 2 which you can't factor but then you ...